Parallel genetic and phenotypic differentiation of Erigeron annuus invasion in China - Yuan-Yuan Liu; Qin-Fen Yang; Zhen Li; Zhi-Xiang Zhou; Xue-Ping Shi; Yong-Jian Wang (Frontiers in Plant Science, 2023)
IntroductionThe factors that determine the growth and spread advantages of an alien plant during the invasion process remain open to debate. The genetic diversity and differentiation of an invasive plant population might be closely related to its growth adaptation and spread in the introduced range. However, little is known about whether phenotypic and genetic variation in invasive plant populations covary during the invasion process along invaded geographic distances.MethodsIn a wild experiment, we examined the genetic variation in populations of the aggressively invasive species Erigeron annuus at different geographical distances from the first recorded point of introduction (FRPI) in China. We also measured growth traits in the wild and common garden experiments, and the coefficient of variation (CV) of populations in the common garden experiments.Results and discussionWe found that E. annuus populations had better growth performance (i.e., height and biomass) and genetic diversity, and less trait variation, in the long-term introduced region (east) than in the short-term introduced region (west). Furthermore, population growth performance was significantly positively or negatively correlated with genetic diversity or genetic variation. Our results indicate that there was parallel genetic and phenotypic differentiation along the invaded geographic distance in response to adaptation and spread, and populations that entered introduced regions earlier had consistently high genetic diversity and high growth dominance. Growth and reproduction traits can be used as reliable predictors of the adaptation and genetic variation of invasive plants.